Multidisciplinary approach to epizootiology and pathogenesis of bat rabies viruses in the united states - Ellison, J. A.; Johnson, S. R.; Kuzmina, N. K.; Gilbert, A. T.; Carson, W. C.; Blanton, J. D.; VerCauteren, K.; Rupprecht, C. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Zoonotic disease surveillance is typically initiated after an animal pathogen has caused disease in humans. Early detection of potentially high-risk pathogens within animal hosts may facilitate medical interventions to cope with an emerging disease. To effectively spillover to a novel host, a pathogen may undergo genetic changes resulting in varying transmission potential in the new host and potentially to humans. Rabies virus (RABV) is one model pathogen to consider for studying the dynamics of emerging infectious diseases under both laboratory and field conditions. The evolutionary history of RABV is characterized by regularly documented spillover infections and a series of notable host-shifts. Within this context, enhanced field surveillance to improve detection of spillover infections will require validated techniques to non-invasively differentiate infected from non-infected individuals. In this study we evaluate the use of infrared thermography to detect thermal changes associated with experimental RABV infection in big brown bats (Eptesicus fuscus) in a captive colony. Our results indicated that 62% of rabid bats had detectable facial temperature decreases (-4.6°C, SD ±2.5), compared to preinoculation baseline values. These data suggest potential utility for discriminating rabid bats in natural field settings. In addition, focusing upon RABV circulating in the United States between 2008 – 2012, we confirmed spillover events of bat RABV among carnivores and identified cross-species transmission events caused by four lineages of RABV associated with insectivorous bats. This study provides a glimpse into RABV pathobiology and spillover dynamics among and between bats and a variety of mesocarnivores.